Acceptability of Covid-19 Vaccine among Frontline Health Care Workers in North Central and South Western, Nigeria - Jimoh, SAKA Mohammed; Kehinde, Oloyede Hassan; Emmanuel, OPOWOYE Segun; Ahmed, ABDULLAHI (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: To explore the acceptability of COVID-19 vaccines among frontline health workers in Nigeria. METHODOLOGY: A descriptive cross-sectional multi-centre survey was conducted among 115 randomly selected frontline health workers in two tertiary health facilities; Federal Medical Centre Abeokuta (South -Western, Nigeria) and University of Ilorin Teaching Hospital (North Central, Nigeria). The inclusion criteria were Frontline Healthcare Workers over the age of 18 years who gave consent for the study, while other hospital workers were absent from work and those unwilling to participate in the study. Data analysis was done using SPSS version 23. RESULTS: Accordingly, 59.1% of respondents accepted to be vaccinated with the COVID-19 vaccine when it becomes available. The level of acceptance increased with the effectiveness and safety of the vaccine. More respondents were also willing to wait 6 months to receive the vaccine than those willing to accept the vaccine at the moment. The age of respondents was statistically significant in the willingness to accept the vaccine. CONCLUSION: The acceptability of the COVID-19 vaccine among health workers increased with the effectiveness of the potential vaccines as well as the duration of vaccine usage. Trusted policymakers can be used for advocacy in combatting the misinformation on COVID-19 vaccines. KEYWORDS: COVID-19, Vaccine-acceptability, Frontline-Health-workers, vaccine-efficacy, Vaccinemisinformation, pandemic